THE FARMING AND MARKETING OF ORGANIC LETTUCE: STUDY AT BOBOSAN VILLAGE, KEDUNGBANTENG SUB-DISTRICT, BANYUMAS - irine Kartika Eka Wijayanti; Indah Widyarin; Ratna Satriani (Fakultas Pertanian, Universitas Janabadra, 2017)
Banyumas has great potential as a producer of organic lettuce in term of condition of natural, human resources and availability of market. The centre producer of organic lettuce is located in district of Kedungbanteng, and managed by farmers group